EVALUATION OF THE VILLAGE ASSET MANAGEMENT SYSTEM (SIPADES) POLICY IN THE VILLAGE GOVERNMENT OF LARANGAN, CANDI DISTRICT - Fazri, Aisyah Nur; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The Village Asset Management System (SIPADES) is an application developed by the Ministry of Home Affairs that aims to increase transparency and accountability in village asset management. However, in early 2024, SIPADES was updated to version 3.0 to address weaknesses in the previous version. However, in its implementation in the field, the SIPADES application in various villages, including Larangan Village, Candi District, still faces several obstacles. This study aims to evaluate SIPADES after the version 3.0 update using William N. Dunn's evaluation theory, which includes aspects of effectiveness, efficiency, adequacy, equity, and responsiveness. Method: The research method used is descriptive qualitative with purposive sampling technique, involving village officials as key informants. Results: The research results show that SIPADES helps in recording village assets to be more orderly and efficient, but still faces technical obstacles such as unstable application access, limited human resources, and a lack of ongoing training. Novelty: Thus, SIPADES version 3.0 is not yet fully optimal, but still has the potential to improve the governance if village assets supported by technical improvements and increased user capacity.